2011
DOI: 10.1021/jf1044102
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Plant Sterols in Ingredients Used in Functional Foods

Abstract: The content of plant sterol (PS) and their oxidation products (POPs) in eight ingredients used to enrich functional foods was studied. A gas chromatographic (GC) technique with mass-spectrometric detection was used for identification, while GC with a flame ionization detector (GC-FID) was used for quantification. β-Sitosterol was the most abundant phytosterol, and the main POPs found were derived from this compound (7α/β-hydroxysitosterol, 7-ketositosterol, and sitostanetriol). The total amount of POPs found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
59
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 29 publications
8
59
0
Order By: Relevance
“…The differences found in the sterol profile in PS-enriched foodstuffs in the literature in comparison with our own samples could be attributed to the origin of the sterols used in enrichment, as recently confirmed by González-Larena et al (2011) in several PS ingredients. In two studies with orange juices, samples enriched with esterified PS (Mezine et al, 2003) (PS origin not specified) and PS from vegetable oils (Devaraj, Jialal, & Vega-López, 2004), a PS profile in which the predominant representative was β-sitosterol (40-50%) in a proportion lower than that found in our study (see Table 2) was reported.…”
Section: Determination Of Plant Sterolssupporting
confidence: 75%
See 4 more Smart Citations
“…The differences found in the sterol profile in PS-enriched foodstuffs in the literature in comparison with our own samples could be attributed to the origin of the sterols used in enrichment, as recently confirmed by González-Larena et al (2011) in several PS ingredients. In two studies with orange juices, samples enriched with esterified PS (Mezine et al, 2003) (PS origin not specified) and PS from vegetable oils (Devaraj, Jialal, & Vega-López, 2004), a PS profile in which the predominant representative was β-sitosterol (40-50%) in a proportion lower than that found in our study (see Table 2) was reported.…”
Section: Determination Of Plant Sterolssupporting
confidence: 75%
“…Then, after phase separation, the chloroform phase was concentrated in a rotary evaporator and dried with nitrogen. The lipid fraction obtained (75 mg approximately) was processed by the method described by González-Larena et al (2011). Briefly, IS (2 mg of epicoprostanol) was added to the lipid fraction and hot saponification (3 mL of 1 N KOH in methanol at 65°C during 1 h) was performed.…”
Section: Determination Of Plant Sterolsmentioning
confidence: 99%
See 3 more Smart Citations